(untitled) (Clinics, 2013)
OBJECTIVE: Fetuin-A is a protein secreted from the liver that inhibits arterial calcification deposition and can contribute to insulin resistance. Hyperthyroidism is also associated with insulin resistance. It is not known whether hyperthyroidism has an effect on fetuin-A levels. METHODS: We measured fetuin-A levels and homeostasis model of assessment-insulin resistance before hyperthyroidism treatment was initiated and after euthyroidism was achieved. A total of 42 patients diagnosed with hyperthyroidism were enrolled in this study. Fetuin-A, insulin, high-sensitivity C-reactive protein, fasting blood glucose, free T3 (fT3), free T4 (fT4), and thyrotropin were measured before and after euthyroidism was established. RESULTS: Basal fasting blood glucose, high-sensitivity C-reactive protein, insulin, c-peptide, homeostasis model of assessment-insulin resistance, fT3, fT4 and fetuin-A levels were significantly decreased after euthyroidism was achieved (Table 1). Basal fasting blood glucose (r:0.407, p:0.008), high-sensitivity C-reactive protein (r:0.523, p